(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Aims: To evaluate the information content of Pathology reports of surgically resected Colorectal Cancer specimens issued by different histopathologists. Methods: All reports of colorectal cancer resection specimens during the years 2011-12 at DHQ level hospital were evaluated against: (a) standards previously agreed as desirable by histopathologistsand (b) standards considered to be the minimum required for informed patient management. Results: 300 reports were evaluated. There was considerable variation in the completeness of reporting of individual items of information. While many items were generally well reported, only 52% (156/300) of rectal cancer reports commented on the completeness of excision at the circumferential resection margin and only 30% (90/300) of all reports stated the number of involved lymphnodes. All of the previously agreed items were stated in only 11% (33/300) of reports on colonic tumors and 4.0%(12/300) of reports on rectal tumors. Seventy eight per cent (234/300) of colonic carcinoma reports and 47% (141/300) of rectal carcinoma reports met the minimum standards. Conclusion: The informational content of many routine pathology reports oncolorectal cancer resection specimens is not sufficient for quality patient management and for cancer registration. Template proforma reporting using nationally agreed standards is recommended as a remedy for this, along with review of laboratory practices in the light of current knowledge and motivation of pathologists through their involvement in cancer management teams.